2015
DOI: 10.1371/journal.pbio.1002202
|View full text |Cite
|
Sign up to set email alerts
|

Lactate Regulates Metabolic and Pro-inflammatory Circuits in Control of T Cell Migration and Effector Functions

Abstract: Lactate has long been considered a “waste” by-product of cell metabolism, and it accumulates at sites of inflammation. Recent findings have identified lactate as an active metabolite in cell signalling, although its effects on immune cells during inflammation are largely unexplored. Here we ask whether lactate is responsible for T cells remaining entrapped in inflammatory sites, where they perpetuate the chronic inflammatory process. We show that lactate accumulates in the synovia of rheumatoid arthritis patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
490
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 563 publications
(529 citation statements)
references
References 48 publications
15
490
0
5
Order By: Relevance
“…In contrast to glucose, lactate levels were increased, and other metabolites may also be affected. Elevated lactate can impair T cells (11,35) and may also contribute to T cell metabolic dysfunction. Similarly, PD-1 was elevated on ccRCC CD8 TIL and may impair T cell metabolism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to glucose, lactate levels were increased, and other metabolites may also be affected. Elevated lactate can impair T cells (11,35) and may also contribute to T cell metabolic dysfunction. Similarly, PD-1 was elevated on ccRCC CD8 TIL and may impair T cell metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…While tumor cells can deplete nutrients (10,15,24,34), no decrease in interstitial glucose levels was observed in ccRCC tumors relative to adjacent normal kidney tissue ( Figure 3A). Nevertheless, lactate can inhibit T cell function (11,35) and was increased in ccRCC interstitial fluid. ccRCC CD8 TIL had normal or a trend toward increased expression of glucose transporter Glut1 and hexokinase 2 (HK2) ( Figure 3B).…”
Section: Cd8mentioning
confidence: 99%
“…Murine T cells were isolated from lymph nodes of C57BL/6 WT mice and activated for 3 days in 24 wells plates coated with anti-CD3 (1 μg/ml) and anti-CD28 (5 μg/ml) antibodies (BioLegend), and containing IL-2 (10 ng/ml; PeproTech) as previously described (15).…”
Section: Murine T Lymphocytes Migration On Isolated Primary Microvascmentioning
confidence: 99%
“…In this regard, the discovery of leptin, one of the most abundant adipocyte-derived hormones controlling food intake and metabolism, has suggested that an organism's nutritional status can control immune selftolerance [16]. Recently, metabolites, such as succinate, citrate and lactate, all intermediate and end products of metabolic pathways, have been shown to activate signaling, resulting in the modulation of immune functions [17][18][19]. …”
mentioning
confidence: 99%
“…Therefore, activated immune and cancer cells relying mainly upon glycolysis need to increase their uptake of glucose to remain viable and functional [22,23]. This selective utilization of glycolysis even in the presence of oxygen is known as "aerobic glycolysis" or the "Warburg Effect" and although it was originally referred only to the peculiar metabolism adopted by rapidly proliferating cancer cells, it has since been observed in specialized immune cells such as lymphocytes and MUs [18,24]. As a consequence of hypoxic or aerobic glycolysis, lactate is produced and accumulates in the extracellular space.…”
mentioning
confidence: 99%